Examining the key features of specialist health service provision for women with Female Genital Mutilation/Cutting (FGM/C) in the Global North: a scoping review - Albert, Juliet; Wells, Mary; Spiby, Helen; Evans, Catrin (Frontiers in Global Women's Health, 2024)
Health care for women with Female Genital Mutilation/Cutting (FGM/C) in the Global North is often described as sub-optimal and focused on maternity care. Specialist FGM/C services have emerged with little empirical evidence informing service provision. The objective of this scoping review is to identify the key features of FGM/C specialist care.The review was conducted in accordance with JBI methodology. Participants: organisations that provide specialist FGM/C care. Concept: components of specialist services. Context: high-income OECD countries. Eligibility criteria included primary research studies of any design from 2012-2022, providing a comprehensive description of specialist services. Seven bibliographic databases were searched (MEDLINE, EMBASE, CINAHL, Web of Science, SCOPUS, Cochrane Library and MIC). The components of 'specialist' (as opposed to 'generalist') services were defined and then applied to an analysis of